Determinants of attendance frequency to flamenco shows in Spain: A cultural economic approach; Determinantes de la frecuencia de asistencia a espectáculos de flamenco en Espa\~na: Un enfoque económico cultural - Jesús Heredia-Carroza; Luis Palma Martos; Alejandro Marín (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2020)
This article aims to determine which variables have effect on the attendance frequency to live flamenco shows. Firstly we have done interviews to flamenco and music industry experts to achieve new-fangled variables in our analysis. Secondly, these variables were valued by flamenco consumers through surveys. Afterwards, with these data, we used a methodology based on different econometric models to obtain the coefficients of the variables. The results show how variables such as educational level, the way the music is listened or the valuation of the performer, amongst others, have an influence on the attendance frequency to flamenco live shows. The article contributes to the scarce empirical literature relating attendance frequency determinants to traditional popular genres by adding never studied before variables, focusing on the flamenco case.
Keywords: C2; D2; Z1; 330; live music; attendance frequency; traditional popular music; flamenco; Spain